TRADISI PARAWANTEN DI DESA KADUHAUK (STUDI LIVING HADIS) DENGAN PENDEKATAN INTERAKSIONISME SIMBOLIK - Deni Firdaus; Muhammad Alif (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the Parawanten tradition in Kaduhauk Village, Banjarsari District, Lebak Regency as a living hadith phenomenon through a symbolic interactionism approach. The research focuses on the practice of giving chickens to paraji (traditional birth attendants) as a form of appreciation for services, almsgiving, and requests for prayers, as well as on how hadith values are lived and interpreted within this tradition. This study employs a qualitative descriptive-interpretative method, with data collected through participant observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, consisting of paraji and community members directly involved in the implementation of the Parawanten tradition. The findings reveal that the community does not refer to hadith texts explicitly, but rather internalizes their substantive values in the form of institutionalized social ethics. The chicken functions as a symbolic representation of hurip (a prosperous and blessed life), reciprocity for good deeds, inclusive almsgiving, and a medium for maintaining social bonds. Through ongoing social interaction and intergenerational transmission, hadith values related to gratitude, reciprocating kindness, charity, and prayer are embedded in local cultural practices. Theoretically, this study contributes to the development of living hadith studies by emphasizing the role of cultural symbols as media for the actualization of hadith values. Practically, it offers contextual insights that can support cultural-religious dialogue and the formulation of policies grounded in local wisdom